Phytochemicals from Phyllanthus niruri Linn. and their pharmacological properties: a review - Bagalkotkar, Gururaj; Sagineedu, Sreenivasa Rao; Saad, Mohd Said; Stanslas, Johnson (Royal Pharmaceutical Society of Great Britain, 2006)
This review discusses the medicinal plant Phyllanthus niruri Linn. (Euphorbiaceae), its wide variety of phytochemicals and their pharmacological properties. The active phytochemicals, flavonoids, alkaloids, terpenoids, lignans, polyphenols, tannins, coumarins and saponins, have been identified from various parts of P. niruri. Extracts of this herb have been proven to have therapeutic effects in many clinical studies. Some of the most intriguing therapeutic properties include anti-hepatotoxic, anti-lithic, anti-hypertensive, anti-HIV and anti-hepatitis B. Therefore, studies relating to chemical characteristics and structural properties of the bioactive phytochemicals found in P. niruri are very useful for further research on this plant as many of the phytochemicals have shown preclinical therapeutic efficacies for a wide range of human diseases, including HIV/AIDS and hepatitis B.